Edukasi dan Deteksi Dini Anemia Pada Remaja Putri di Desa Mireng, Trucuk, Klaten: Upaya Mendukung Desa Ramah Perempuan dan Anak - Catur Bayu Aji; Ammarsyaid Abdulhafizh; Amanda Zahra Arfityaningrum; Umi Wakhidaturrokhimah; Rizki Setyo Wilastri; Fatiya Izatuz Zahra; Nur Aviva Azzahro; Rizwan Hamid Arief; Livia Putri Anggraini; Najwa Khairina Nafisa; Mutiara Rahma Siregar; Sabariyanto Sabariyanto (Abdimas Indonesian Journal, 2026)
Anemia continues to be one of the major health issues among teenage girls in Indonesia, with a national prevalence of 32% among those aged 15–24, which impacts their ability to concentrate in school, their productivity, and their quality of life. The activity was held on July 8, 2026, at the Harapan Indah V Community Health Post (Posyandu) in Dayan Village, in collaboration with the Trucuk I Public Health Center (Puskesmas) and local health workers. This study employed a descriptive method with a qualitative approach through observation, interviews, and literature review. Educational materials covered the definition, causes, signs and symptoms, and impacts of anemia, as well as prevention efforts through a nutritious diet and adherence to iron supplement intake. The activity was attended by teenage girls from Dukuh Gecekan, Paesan, and Dayan, who actively participated in the question-and-answer sessions and discussions. The results of the activity showed an increase in participants’ understanding of anemia prevention and the importance of early detection of reproductive health issues among adolescents. This activity serves as a concrete strategy to support the fulfillment of young women’s reproductive health rights at the village level, in line with the DRPPA program’s performance indicators.